Sitting Behaviour in Home Working Environment and its Association with Back Pain during Pandemic in Malaysia - Teh Phoey Lee; Ker Woon Choy; Low Yeh Ching; Ooi Pei Boon (UiTM Press, 2022)
Introduction: COVID-19 pandemic leads to working from home culture. Long hours of the static sitting posture on improper chairs at home may lead to low back pain (LBP). This study aims to study the prevalence of LBP in sitting position during usage of portable computing devices and the association of LBP and sitting behaviour in home environment settings. Methods: An online questionnaire cross-sectional study was conducted, and the Visual Analog Scale (VAS) and Modified Oswestry LBP Disability questionnaire were adapted. The association between the factors such as duration of chair break, type of posture and the incidence of LBP were examined. Results: Majority of the 279 participants who participated in the study experienced LBP while working from home. We found strong evidence for suggesting a significant statistical association between duration of chair break (chi-squared value = 19.86, p-value = 0.006) and LBP. Most of the participants were categorised as having minimal disability, followed by moderate disabilities and only around 1% were crippled. ODI for sitting posture was statistically significant (Za value = 16.35, p = 0.022). Posture with round back and increased kyphosis with the feet supported on the floor is the highest reported posture with VAS score. VAS for duration of sitting posture was statistically significant (Za value = 10.37, p = 0.035). Those who spent only 5 - 30 minutes in the posture reported significantly lower VAS score compared to more than 30 minutes in the posture. Conclusion: Correct posture and taking chair breaks are essential to reduce the incidents of back pain and functional disabilities within the home working environment. The outcome of our research can be evidence-based information to occupational health specialists to optimise the current standard of practice and guidelines in working from home management.